IMPROVEMENT OF MECHANISMS OF PUBLIC MANAGEMENT OF UKRAINE'S EUROPEAN INTEGRATION PROCESSES IN THE CONDITIONS OF EU ACCESSION NEGOTIATIONS (Coordinates of Public Administration, 2026)
The article examines the mechanisms of public management of Ukraine's European integration processes at the stage of transition from the implementation of the Association Agreement to the full preparation of the state for membership in the European Union. The relevance of the topic is due to the fact that after obtaining candidate status and opening accession negotiations, the burden on the public administration system has become qualitatively different: the government, parliament and central executive authorities are required not only to adapt individual regulatory acts to the EU acquis, but also to build a long-term sustainable accession management architecture that combines strategic planning, interdepartmental coordination, staffing, financing, digital monitoring, parliamentary control and communication with European institutions. The paper analyzes the current institutional structures, including the role of the government center, relevant deputy ministers, interagency mechanisms, and the parliamentary circuit; characterizes the legislative framework - from the constitutional consolidation of the strategic course for EU membership to the Law «On Administrative Procedure», roadmaps for Cluster 1, acts on the negotiation architecture, and the National Program for Adapting Ukrainian Legislation to EU Law. Particular attention is paid to financial instruments, primarily the Ukraine Facility, public investment management reform, the link between strategic planning and the budget, as well as the issues of human resource capacity and digital human resource management systems. Based on the reports of the European Commission, OECD/SIGMA materials, documents of the Government of Ukraine, the Verkhovna Rada of Ukraine, the National Agency for the Supervision of Civil Service, and analytical and scientific works, it was established that the key weaknesses of the current model are the fragmentation of evidence-based policymaking, the insufficient quality of legislative preparation, the slow restoration of the meritocratic civil service, the shortage of personnel in the European integration units, the weak connection of reform monitoring with the budget cycle, and the need for stronger executive-parliamentary synchronization. A comparative analysis of the practices of Croatia, Estonia, and Poland made it possible to show that effective management of EU accession relies on a formalized division of functions between the political leadership, technical secretariat, working groups, and parliamentary committees, as well as on a stable professional bureaucracy and the mandatory systematic procedures for coordinating positions. It is substantiated that the following are priorities for Ukraine: institutionalization of a two-tier system of EU accession management; transformation of the National Adaptation Program into a single planning and monitoring tool; completion of the reform of labor remuneration and selection for the civil service; integration of digital monitoring tools with budgeting and personnel systems; creation of a permanent «government-parliament» mechanism for monitoring the acquis; and strengthening regional readiness for future membership. The article concludes with a practical plan for implementing the recommendations, indicating the deadlines, responsible institutions and resource base.